ANALYSIS OF THE PRACTICE OF IDENTIFYING LOW-INCOME FAMILIES AND PROVIDING TARGETED ASSISTANCE TO THEM - Sholdarov Dilshod Azimiddin ugli (Scholar Express Journals, 2024)
In the article, the number of people in need of social protection in the regions, the number of families with many children, the number of families with persons with disabilities, the number of families in the region and the funds allocated to them in the state budget for social benefits, the number of low-income families and the funds allocated to them, as well as the work carried out in the field of social protection of the population and the analysis of their practice is given
Keywords: State social policy; social protection; social services; pension provision